Ang Bagong Lipunan, 1972-1986: Isang Panimulang Pag-aaral sa Musika at Lipunan* - Navarro, Raul C. (Humanities Diliman: A Philippine Journal of Humanities; Vol 5 No 1&2 (2008), 2009)
The essay shows the vital role of music in shaping Filipino consciousness. The Spaniards used music to introduce the Catholic faith while for the Americans, it was a vehicle to teach English in the Philippine public school system. The importance of music in nation-building is particularly evident in the Marcos period where this was used as an ideological tool for promoting the tenets of the New Society. The discourse of the New Society was introduced in both public and private schools through music, and propagandistic songs dominated the airwaves and television. However, music became an instrument for a counterdiscourse in the twilight of the New Society. Such music was played in underground radio programs during the Marcos era, but this was later mainstreamed when the dictator was exiled in Hawaii.
Keywords: New Society, discourse, counter-discourse, institution, classroom